Pengembangan Sistem Informasi Magang untuk Membantu Proses Administrasi Siswa Magang (Studi pada: Badan Kepegawaian Negara) - Brian Nur Islahuddin; Satrio Agung Wicaksono; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Badan Kepegawaian Negara is a government agency that has the task of carrying out governmental tasks in the field of state staff management. Badan Kepegawaian Negara accommodates students who want to do an internship. There were several obstacles in organizing internship activities, namely the internship registration that requires the internship candidate to come to the office of Badan Kepegawaian Negara, the recapitulation of the internship students that were separated, and monitoring the daily activities of the internship students that were difficult. The problems existed in the internship activities could hamper the administrative processes of internship students, so this research aimed to build an internship information system that could help the administrative processes. The internship information system development used waterfall approach. In this research, the problem related to administration processes of the internship students can be made easier by adding, eliminating, or changing the current business process (as-is) to a proposed business process (to-be) to produce features in the internship information system that was built with the laravel framework. The internship information system that has been build was then tested using the user acceptance test approach to measure the level of user acceptance of the internship information system features, the flow of activity on the internship information system, and the interface of the internship information system. The results of the user acceptance test showed the number 92,39% which showed the user accepted the information system and the features inside the system.